Pengaruh Kepemimpinan Transformasional Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Mitramas Muda Mandiri - Gumelar, Bagja; Jamaludin, Asep; Nandang, Nandang (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
High employee quality determines the company overall performance and contribution to success. In addition to transformational leadership, good employee performance requires a high level of work discipline, which affects employee productivity. The goal is to know the work disipline and transformational leadership impacted the employees’ performance. This study employs linear multiple regression analysis and quantitative with SPSS 25 to conduct hypothesis testing. The result shows transformational leadership improved the worker performance with the t-count value 6.210> t-table 1.683 and the significance level 0.000 (<0.05). The employee performance impacted with work dicipline, where t-count is 2.113 > t-table 1.683 and the significance is 0.041 (<0.05) on PT. Mitra Muda Mandiri . The transformational leadership and work discipline influence employee performance, F-count value of 23.170 > F-table 3.230 and sig values is 0.000 (0.05). So, transformational leadership and work discipline has significantly affected the employee performance.